Analysis of Travel Experience Quality at City Destinations - Yeni Yuniawati; Oce Ridwanudin (Institut Pariwisata dan Bisnis Internasional, 2015)
Bandung is one of the many destinations which could be categorised as urban tourism or urban travel destinations. These destinations have different characteristics compared to other types destinations, therefore the experience gained by tourists during visits would be different. This study aims to create a means of measuring the quality of the tourist experience viewed from three phases of travel experience, namely pre-travel phase measured by information search construct, planning, decision making; experiential phase, measured with product attributes, interaction and involvement constructs; and Recollection phase, measured by these constructs: meaning, satisfaction, storing, sharing, and Recollection. The research method is descriptive and verification using factor analysis data analysis techniques. Data were obtained through interviews and questionnaires to tourists who visit the city of Bandung as many as 200 people. The results showed that the proposed model is valid and reliable for measuring the travel experience.